Crisis of conscience - Biman Prasad (Asia Pacific Network, 2001)
The Univesity of the South Pacific has become the centre of excellence in the region, as indeed any university of USP's nature should be. Apart from teaching and research, the university has in many ways become the critical conscience of the region.